An unbiased high‐throughput drug screen reveals a potential therapeutic vulnerability in the most lethal molecular subtype of pancreatic cancer. Issue 8 (4th July 2020) - Pan, Chun‐Hao; Otsuka, Yuka; Sridharan, BanuPriya; Woo, Melissa; Leiton, Cindy V.; Babu, Sruthi; Torrente Gonçalves, Mariana; Kawalerski, Ryan R.; K. Bai, Ji Dong; Chang, David K.; Biankin, Andrew V.; Scampavia, Louis; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is predicted to become the second leading cause of cancer‐related deaths in the United States by 2020, due in part to innate resistance to widely used chemotherapeutic agents and limited knowledge about key molecular factors that drive tumor aggression. We previously reported a novel negative prognostic biomarker, keratin 17 (K17), whose overexpression in cancer results in shortened patient survival. In this study, we aimed to determine the predictive value of K17 and explore the therapeutic vulnerability in K17‐expressing PDAC, using an unbiased high‐throughput drug screen. Patient‐derived data analysis showed that K17 expression correlates with resistance to gemcitabine (Gem). In multiple in vitro and in vivo models of PDAC, spanning human and murine PDAC cells, and orthotopic xenografts, we determined that the expression of K17 results in a more than twofold increase in resistance to Gem and 5‐fluorouracil, key components of current standard‐of‐care chemotherapeutic regimens. Furthermore, through an unbiased drug screen, we discovered that podophyllotoxin (PPT), a microtubule inhibitor, showed significantly higher sensitivity in K17‐positive compared to K17‐negative PDAC cell lines and animal models. In the clinic, another microtubule inhibitor, paclitaxel (PTX), is used in combination with Gem as a first‐line chemotherapeutic regimen for PDAC. Surprisingly, we found that when combined with Gem, PPT, but not PTX, was synergistic in inhibiting the viability of K17‐expressing PDAC cells. Importantly, in preclinical models, PPT in combination with Gem effectively decreased tumor growth and enhanced the survival of mice bearing K17‐expressing tumors. This provides evidence that PPT and its derivatives could potentially be combined with Gem to enhance treatment efficacy for the 50% of PDACs that express high levels of K17. In summary, we reported that K17 is a novel target for developing a biomarker‐based personalized treatment for PDAC. Abstract : Keratin 17, a signature gene overexpressed in the most lethal subtype of pancreatic ductal adenocarcinoma (PDAC), is both prognostic and predictive, and it directly promotes chemoresistance. We discover a novel therapeutic regimen that provides higher efficacy for Keratin 17‐expressing PDAC. These studies bring us closer to the frontline of translational research to develop a biomarker‐based targeted therapy for cancers.